2020
DOI: 10.2460/javma.257.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with job satisfaction and engagement among credentialed small animal veterinary technicians in the United States

Abstract: S everal studies 1-4 have revealed positive correlations between job satisfaction and quality of life, physical health, and mental health, particularly in health-care workers. Veterinary technicians, specifically those credentialed to practice under the oversight of an organization or state board, experience a variety of stressors in the workplace, yet to the authors' knowledge, no studies have been performed to examine job satisfaction or engagement among veterinary technicians. According to the 2018 American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Most participants also believed that taking on additional AMS responsibilities could benefit them professionally and empower them within the practice. Studies have suggested that underutilization of training and skills contributes to veterinary technician job dissatisfaction [ 21 , 22 ] Opportunities to build knowledge and skills, solve complex problems, and have a sense of autonomy have been linked to lower rates of burnout among veterinary technicians [ 22 , 23 ]. While work hours and salaries are critical drivers of retention, attrition of veterinary technicians is lower among those who feel their work is meaningful and valued [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most participants also believed that taking on additional AMS responsibilities could benefit them professionally and empower them within the practice. Studies have suggested that underutilization of training and skills contributes to veterinary technician job dissatisfaction [ 21 , 22 ] Opportunities to build knowledge and skills, solve complex problems, and have a sense of autonomy have been linked to lower rates of burnout among veterinary technicians [ 22 , 23 ]. While work hours and salaries are critical drivers of retention, attrition of veterinary technicians is lower among those who feel their work is meaningful and valued [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other critical barrier identified for veterinary technician AMS engagement was the substantial time constraints of daily practice. Time constraints and staffing shortages are well-documented concerns among veterinary technicians throughout studies of well-being and job satisfaction [ 21 , 22 , 24 , 38 ]. Currently, the veterinary profession in the United States is facing a significant shortage in the veterinary technician workforce [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liss et al 60 published a study with 873 CVT respondents and investigated job satisfaction and individual engagement among CVTs. The results showed a mean value for CVT job satisfaction of 5.4 (1 = extremely dissatisfied and 7 = extremely satisfied).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…High levels of responsibility to provide often life-saving health care to animals combined with having to manage the owners' expectations and irregular working hours can cause considerable levels of work-related stress ( 1 ). A relatively limited number of studies have investigated work satisfaction and engagement among veterinarians across the globe ( 2 4 ). These confirm that individuals working in the veterinary profession are regularly affected by their chosen profession.…”
Section: Introductionmentioning
confidence: 99%